An Error Analysis on the Use of Past Tense in Recount Text by 6th Grade Elementary Students - Dinda Ismu Asyifa; Muhammad Fikri Yazid (Faculty of Letters Universitas Balikpapan, 2023)
Writing is a difficult skill in English learning. It is not easy to have a good skill in writing because writing is an activity that needs more concentration and practice. In addition, students must know the English grammar rule in writing a text. The difficulties in writing can cause the students to make errors in their writing. When the students have limited knowledge about grammar and vocabulary, they will make errors in making sentences. The structure of the sentences will be inappropriate according to the structure rules and the meaning will be not clear. The errors occur in the students’ writing not only in grammar and vocabulary but also in expressing their ideas in English. This research aimed to find out typical errors on 6th grade elementary school students in writing recount text. However, researchers took primary data to obtain the result. There were 65 students writing recount text for this research. Qualitative approach was used for this research. The result stated that most students made errors on grammar aspects (noun, verb, determinant/article, preposition) with a percentage of 55,03%. Next, students made errors on punctuation which is 27,96%. Lastly, students made an error on spelling only 17,0%.